On the rare species of a population - Yatracos, Yannis G. (My University, 1995)
Based on a search of size n in a population, a predictor is proposed for the total probability of observing a rare species in additional searches of size N, that has the same expectation with it. The predictor is based on one additional search as in Robbins (Ann. Math. Statist. (1968) 256-257) and its mean squared error is computed in order to determine its accuracy or construct confidence intervals.
Keywords: Population; Accuracy